Pemetaan Pembelajaran Sejarah Bermuatan Lokal Materi Kerajaan Hindu-Budha di Sumatera Barat - Sauma, Syifa; Aisiah, Aisiah (Jurnal Kronologi, 2024)
ABSTRACT This research aims to map history learning with local content on Hindu-Buddhist kingdom material in West Sumatra in history subjects in high school phase E (class X) in terms of curriculum needs and teacher needs. The research method uses a quantitative and qualitative descriptive approach (Mix Methods). The research data source came from a Google form filled in by 17 SMA/MA history teachers in West Sumatra and the results of interviews with history teachers at SMA Negeri 12 Padang. Data analysis was carried out quantitatively using percentages (%) and descriptively qualitatively. The findings of this research are, 1) the majority (72%) of high school/MA history teachers in West Sumatra have not carried out local content history lessons, 2) if we look at the availability of textbooks, the majority of teachers admit that textbooks are not yet available in schools, 3) most teachers use sources from the internet, 4) the models and methods used by teachers are problem based learning and group discussions. Keyword: Mapping, History Learning, Local Content.